Design and Development of Automatic Micro Controller based Weather Forecasting Device - V, Bindhu (Journal of Electronics and Informatics, 2020)
The entailment for weather forecasting to take the essential pre-cautious measures in our regular routines and elude the unwanted fatalities has made this more attractive area of research. Particularly in the rural areas the weather forecasting enables the farmers to have an effective crop management, avoiding the destruction in the crops and increasing the yield. In order to have a real time weather forecasting the proposed method in the paper tries to develop an automatic weather forecasting device based on the microcontroller. The proposed method utilizes the sensors to monitor the weather changes and engages the raspberry pi to process the information gathered and convey it to the end user. The proposed system was tested by implementing it in the Indian delta districts and the accuracy, precision and flexibility in the forecasting was evinced by the data output observed over and done with the Thinkspeak .Web
Keywords: Weather Forecasting; Raspberry Pi; Ethernet; Cloud; Wireless Sensors